Effectiveness of Legal AID Services on Community Property Cases in Marriage at Partner Legal AID Institutions Madani West Sulawesi - Wawan; Zainal Said; Fikri; Sudirman L; Ali Rusdi (Universitas Muhammadiyah Palu, 2024)
This research aims to analyze the problem of free legal assistance for weak and poor communities. These provisions are regulated in the Legal Aid Law, which is the embodiment of Article 27 paragraph (1) and Article 28D paragraph (1) which shows that everyone has the same position before the law and is entitled to legal protection. The state has legally regulated it in such a way that justice can be felt by all levels of society, but the application of the law is still far from justice itself. This research is empirical legal research using a sociological juridical approach, namely an approach that emphasizes research that aims to obtain legal knowledge empirically. The research results show that LBH Mitra Madani, as a structural institution, has provided legal assistance in litigation and non-litigation. Apart from that, LBH Mitra Madani also provides legal counseling, community organizing and training in the legal field. However, the obstacle is the lack of financial support from the government, because LBH Mitra Madani has not yet been accredited. There are 37 cases that have been assisted from 2019 to 2022, of which the cases handled by LBH Mitra Madani are predominantly civil cases. LBH Mitra Madani's obstacles in providing legal assistance include legal substance and legal structure factors. According to regulations, the legal assistance provided by LBH Mitra Madani to poor people should be free. However, in fact, LBH Mitra Madani still collects fees from every client who is given legal assistance, this is because LBH Mitra Madani has not received financial assistance from the Government. Apart from the substantial factors that constrain the effectiveness of LBH Mitra Madani in providing legal assistance, there are legal structure factors, which include law enforcement institutions (police, prosecutors, courts and advocates).